2016
DOI: 10.1080/13880209.2016.1226904
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of Amorphophallus paeoniifolius tuber on experimental ulcerative colitis in rats

Abstract: Context: The tuber of Amorphophallus paeoniifolius (Dennst.) Nicolson (Araceae), commonly called Suran or Jimmikand, has high medicinal value and is used ethnomedicinally for the treatment of different gastrointestinal and inflammatory disorders. Objective: The present study evaluated the effects of extracts of Amorphophallus paeoniifolius tubers on acetic acid-induced ulcerative colitis (UC) in rats. Materials and methods: Wistar rats were orally administered methanol extract (APME) or aqueous extract (APAE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In the current study, intrarectal administration of 3% acetic acid caused induction of UC, and there was marked decrease in BW of animals in colitis group in agreement with the results of the previous studies [1,17]. The BW reduction of animals is indicative of their weakened state due to colitis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the current study, intrarectal administration of 3% acetic acid caused induction of UC, and there was marked decrease in BW of animals in colitis group in agreement with the results of the previous studies [1,17]. The BW reduction of animals is indicative of their weakened state due to colitis.…”
Section: Discussionsupporting
confidence: 80%
“…IBD is a chronic disease that can involve gastrointestinal system. IBD remains a major gastrointestinal health-care issue [1]. The prevalence of IBD has been increasing, and higher incidence rates of IBD are seen in the developed countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…β-Sitosterol has been applied in treating many diseases because of the anti-inflammatory, anti-proliferative and anticancer effects (17,18). However, the effect of BAMBI together with β-sitosterol on cell autophagy and proliferation in NSCLC is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The content of glucomannan in the tuber extracts was also high (Dey et al, 2016). Further, we isolated betulinic acid and β-sitosterol from the tuber extract by column chromatography (Dey et al, 2017a), however, they were identified based on thin layer chromatography. Hence, the present study was conducted to characterize the isolated compounds of A. paeoniifolius tuber extracts and to investigate the effect of tuber extract and its constituents (glucomannan and betulinic acid) on experimental constipation on loperamide-induced constipation in rats and its modulation by standard laxative agent.…”
Section: Introductionmentioning
confidence: 90%